2021
DOI: 10.1084/jem.20210420
|View full text |Cite
|
Sign up to set email alerts
|

A growth factor–expressing macrophage subpopulation orchestrates regenerative inflammation via GDF-15

Abstract: Muscle regeneration is the result of the concerted action of multiple cell types driven by the temporarily controlled phenotype switches of infiltrating monocyte–derived macrophages. Pro-inflammatory macrophages transition into a phenotype that drives tissue repair through the production of effectors such as growth factors. This orchestrated sequence of regenerative inflammatory events, which we termed regeneration-promoting program (RPP), is essential for proper repair. However, it is not well understood how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 132 publications
(216 reference statements)
7
46
0
Order By: Relevance
“…Circulating monocytes scan for pathogens and respond to inflammatory signals needed to perform their phagocytic functions, or monocytes can tissue migrate to become macrophages. The resulting macrophages are not a uniform cell population; and there is significant macrophage heterogeneity determined by the immune environment [ 51 ]. In mice, monocyte derived macrophages are typically classified as either pro-inflammatory M1 (Ly6C Hi ) or M2 (Ly6C Lo ) pro-reparative cells generated following efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating monocytes scan for pathogens and respond to inflammatory signals needed to perform their phagocytic functions, or monocytes can tissue migrate to become macrophages. The resulting macrophages are not a uniform cell population; and there is significant macrophage heterogeneity determined by the immune environment [ 51 ]. In mice, monocyte derived macrophages are typically classified as either pro-inflammatory M1 (Ly6C Hi ) or M2 (Ly6C Lo ) pro-reparative cells generated following efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, monocyte derived macrophages are typically classified as either pro-inflammatory M1 (Ly6C Hi ) or M2 (Ly6C Lo ) pro-reparative cells generated following efferocytosis. The Ly6C Lo macrophages can be divided into three further groups participating in the resolution of inflammation, antigen presentation, and tissue repair, and the later are known to release growth factors and pro-angiogenic and tissue repair factors, such as VEGFA, growth differentiation-factor 3 (GDF3), or insulin-like growth factor-1 (IGF-1) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same animal model, the expression of GDF-15 was induced in the skeletal muscles via PPARβ/δ agonist, mitigating inflammation and improving glucose tolerance ( 39 ). In another mouse model, GDF-15 induction through the PPARγ pathway plays a key role in tissue regeneration ( 40 ). In summary, hindbrain GFRAL acts as a receptor for GDF-15 and may explain part of its metabolic effects, however the mechanisms of its immunomodulatory effect remain to be determined.…”
Section: Cellular Mechanisms and Downstream Signaling Pathways Of Gdf-15mentioning
confidence: 99%
“…A recent detailed analysis of these macrophages by determining their mRNA expressions on a single cell level demonstrated the complexity of this transformation process. 7 The timed switch between the two main subsets of macrophages, the inflammatory ones that produce proinflammatory cytokines and the healing ones that produce growth and angiogenic factors and anti-inflammatory mediators, is a key to the proper regeneration process, and it is thought to be induced by the efferocytosis process itself. This idea came from many previous observations that demonstrated that uptake of apoptotic cells induces an anti-inflammatory phenotype in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…A recent detailed analysis of these macrophages by determining their mRNA expressions on a single cell level demonstrated the complexity of this transformation process. 7 …”
Section: Introductionmentioning
confidence: 99%